DEVELOPMENT AND EVALUATION OF NOVEL DRUG DELIVERY SYSTEM OF TOLTERODINE TARTRATE - Patil, Vijaykumar; Belsare, Deepak (International Journal of Applied Pharmaceutics, 2017)
Objective: Tolterodine tartrate (tolterodine) is used for treating overactive bladder (OAB) with symptoms of urinary frequency, urgency and leakage. Tolterodine is an antimuscarinic (anticholinergic) agent. It works by blocking a chemical that causes contractions of the bladder. Present work involved development of a novel drug delivery system of tolterodine intended to be taken once daily. Methods: Extended release (ER) pellets of tolterodine were prepared and optimized for in vitro drug release. Subsequently, these pellets were filled into a suitable sized capsule. The resulting capsules were evaluated for in vitro drug release. Optimized formulation was subjected to accelerated stability studies for 3 mo and was evaluated for description, average weight, assay and drug release. Results: The optimized ER capsule exhibited similar dissolution profile as that of the reference listed drug (RLD), with approximately 45%, 75% and more than 80% release in 3 h, 5 h and 7 h respectively. Accelerated stability studies indicated good physical and chemical stability of the formulation. Conclusion: ER formulation of tolterodine was optimized and can be used as once a day dosage, reducing the frequency of administration when compared with the immediate release formulation. The developed formulation exhibited similar behavior as that of reference formulation Detrol LA marketed in the US.